Precision FMCW Short-Range Radar for Industrial Applications. - Atayants, Boris A. (Artech House, 2014)
This book describes methods for making accurate radar measurements of short distances in applications where physical contact with materials is impractical. Sources of error are identified, and methods of reducing these errors are described. Practical test procedures for measuring instruments are also provided. Much of the book is dedicated to providing radar engineers with practical applications, detailing the conditions, equipment, and approach of experimental estimation. With the help of computer simulation, the achievable advantages in accuracy of radar range measurement with various approaches are revealed and quantitatively estimated. Readers are also provided with methods of random process theory and mathematical statistics, along with functional analysis and optimization.